Answer:
x=0,-1 and x=
x=\frac{2+\sqrt{10}}{3},\frac{2-\sqrt{10}}{3}x=
3
Step-by-step explanation:
1 Cancel 2 on both sides.
3{x}^{2}+3x=03x
2
+3x=0
2 Factor out the common term 3x3x.
3x(x+1)=03x(x+1)=0
3 Solve for xx.
x=0,-1x=0,−1
1 Move all terms to one side.
3{x}^{2}-3x-1-x-1=03x
2
−3x−1−x−1=0
2 Simplify 3{x}^{2}-3x-1-x-13x
2
−3x−1−x−1 to 3{x}^{2}-4x-23x
2
−4x−2.
3{x}^{2}-4x-2=03x
2
−4x−2=0
3 Use the Quadratic Formula.
x=\frac{4+2\sqrt{10}}{6},\frac{4-2\sqrt{10}}{6}x=
6
4+2√
10
,
6
4−2√
10
4 Simplify solutions.
x=\frac{2+\sqrt{10}}{3},\frac{2-\sqrt{10}}{3}x=
3
2+√
10
,
3
2−√
10